A Survey of Security Threats and Security Management in Cloud Computing - S. P. Lalitha, Dr. A. Murugan (Mathematical Statistician and Engineering Applications, 2022)
The cloud computing is the delivery of computing services which includes the servers, storage, databases, networking, software, analytics, and intelligence over the Internet. The attacks and threats degrade the performance of the cloud computing services. The detection and mitigation of these threats and attacks are very important in all types of cloud services to provide various services to the users through the cloud platform. In this paper, various conventional security methodologies for cloud system are discussed in detail with its limitations and advantages.